Implementasi Fatwa DSN MUI No. 116/DSN-MUI/IX/2017 tentang Uang Elektronik Syariah di KSPPS BMT Bahtera Pekalongan - Akbar Maulana; Makrum Kholil; Muhammad Masruri Ramadhoni (el hisbah: Journal of Islamic Economic Law, 2022)
This study examines the mechanism for electronic money transactions at the BMT Bahtera Pekalongan Cooperative and the DSN MUI Fatwa NO. 116/DSN-MUI/IX/2017 regarding sharia electronic money at the BMT Bahtera Pekalongan Cooperative. This research used field research with a qualitative approach. While the data collection techniques used are observation, interviews, and documentation. The data analysis technique used is qualitative data analysis following the model given by Miles and Huberman with data analysis using data reduction, data presentation, and verification or conclusion. Research results show that the mechanism for electronic money transaction in the BANTERA Mobile application uses a wadiah contract and a mudhorobah contract where customers/members are requited to open a saving book in advace using a udhorobah and wadiah contract. As for the aplication of the DSN MUI Fatwa NO. 116/DSN-MUI/IX/2017 CONCERNING Shariah electronic money, in the first fatwa regarding general provison number 1 point c it states “the nominal amount of electronic money managed by issuers is a deposit as intended in the laws governig banking.